Chronic Pain Syndromes in Gynaecological Practice: Endometriosis and Fibromyalgia - Siedentopf, F. (Geburtshilfe und Frauenheilkunde, 2012)
As gynaecologists frequently function as “general practitioners” for women, gynaecologists are frequently confronted with questions which initially appear to have only a tenuous connection to their field. Chronic pain syndromes represent a particular challenge, especially as pain syndromes are often associated with severe psychosocial stress for the affected woman. This article discusses some of the psychometric aspects of chronic pain in endometriosis and fibromyalgia together with practical therapeutic approaches.
Keywords: Endometriosis; fibromyalgia; psychosomatics